Twitter and politics: a framing analysis of Maryam Nawaz and Imran Khan's social media discourse - Salam-Salmaoui, Rauha; Salam, Shazrah (Frontiers in Communication, 2023)
This study explores the framing strategies employed by influential Pakistani political figures, Imran Khan, and Maryam Nawaz, on Twitter. By adopting Hallahan's (1999Hallahan's ( & 2011) ) framing theory as an analytical framework, we analyze their tweets to reveal how they strategically shape political narratives and influence public perceptions. Our findings provide evidence of Twitter's significant role as a powerful tool for political communication and discourse in the Pakistani context. The study enhances our understanding of the interplay between political communication and political identities, shedding light on the nuanced strategies used by political actors to construct persuasive narratives. This research contributes to the broader landscape of Pakistani political communication and the intersection between social media, politics, and framing strategies.